Comparative analysis of a hybrid Photovoltaic-Water Thermal solar system using monocrystalline, polycrystalline and amorphous silicon solar modules - Kuefouet Lontsi Alexis; Djousse Kanouo Boris Merlain; Tangka Julius Kewir; Aloyem Kazé Claude Vidal; Grisseur Djoukeng Henri (E3S Web of Conferences, 2022)
The proposed work consists of a comparative analysis of a model of a hybrid solar PV/T waterborne system using monocrystalline, polycrystalline and amorphous silicon solar modules. In this work, we have highlighted that the design of a PV/T waterborne system depends on the type of solar module. We have chosen on the market the polycrystalline / monocrystalline silicon solar modules with a power of 100Wc each and 60Wc for the amorphous. Behind each solar module is glued a coil exchanger of respective dimensions: 22m, 32m length and 12 mm diameter for water circulation. The prototypes of the water PVTs as well as their control modules have been realized in the west of Cameroon. Tests were conducted and the data collected led us to optimize the production of the solar photovoltaic modules. We obtained an average daily electrical energy gain of 10.7% or 10.7Wc (mono-crystalline); 13.9% or 13.9Wc (polycrystalline) and 0.97% or 1.62Wc (amorphous) compared to conventional solar panels. For the thermal side, we obtained an average daily thermal power of 214.944 W or 4 liters of hot water (37°C) for the monocrystalline panel; 298.35 W or 5,6 liters of hot water (44.5°C) for the polycrystalline module and 304,57 W or 13.78 liters of hot water (48.6°C) for the amorphous. These tests were made on an average sunshine of 835.51W/m2 between 7h30 min and 15h30 min. The analysis comparison of the developed models shows us that the PVT with poly water has a better electrical output followed by the mono then the amorphous and the PVT with amorphous water has a better thermal output followed by the poly and the mono. This approach allowed us to recover a quantity of the electrical power of the modules lost by Joule effect while determining the quantity of hot water that can be produced by a PV module